Connecting brain and behavior in clinical neuroscience: A network approach. (November 2021) - Blanken, Tessa F.; Bathelt, Joe; Deserno, Marie K.; Voge, Lily; Borsboom, Denny; Douw, Linda
Highlights: Introducing a united framework to bridge the gap between network neuroscience and psychopathological networks. Showcasing three methodological avenues to introduce networks of brain and behavioral data. Creating a common language that allows to exploit synergies. Abstract: In recent years, there has been an increase in applications of network science in many different fields. In clinical neuroscience and psychopathology, the developments and applications of network science have occurred mostly simultaneously, but without much collaboration between the two fields. The promise of integrating these network applications lies in a united framework to tackle one of the fundamental questions of our time: how to understand the link between brain and behavior. In the current overview, we bridge this gap by introducing conventions in both fields, highlighting similarities, and creating a common language that enables the exploitation of synergies. We provide research examples in autism research, as it accurately represents research lines in both network neuroscience and psychological networks. We integrate brain and behavior not only semantically, but also practically, by showcasing three methodological avenues that allow to combine networks of brain and behavioral data. As such, the current paper offers a stepping stone to further develop multi-modal networks and to integrate brain and behavior.